Self-Organized Nanostructures on GaSb(001) Surfaces Due to Low-Energy Ion Irradiation - Saeed, S. R.; Krok, F.; Szymonski, M. (Sulaimani Journal for Pure and Applied Sciences, 2013)
Surface modification of GaSb(001) induced by low energy (2 to 4.5 keV) Ar ion beam irradiation has been investigated by means of atomic force microscopy (C-AFM). It has been found, that depending on the ion beam parameters, i.e. energy and fluence, narrow size distribution of nanostructure patterns have been developed on the irradiated surfaces. Particularly, at incidence angle of 80o with respect to the surface normal, remarkably ordered ripple like structures are formed. The wave vector of the ripple pattern is oriented perpendicular to the direction of the ion beam projection on the irradiated surface. It has been also found, that the surface roughness, in terms of RMS, is initially a decreasing function of the ion fluence, but above medium fluence (of 1×1016 ions/cm2) it increases with the irradiation time. The results are discussed in terms of ballistic processes of sputtering and existing theories describing the ion beam induced surface modification.
Keywords: surface patterning; ion irradiation; ripples; AIIIBV; atomic force microscopy